Starting hop lipidomics - Isolation and characterization of non-polar, neutral and polar hop lipids. - Hop Special - Rettberg, Nils; Thörner, Sarah; Garbe, Leif-Alexander (BrewingScience, 2013)
Lipids are very diverse in chemical structure and properties. They are spread over a wide polarity range, thus comprehensive lipid analysis (lipidomics) from biological samples such as hops is challenging. The current study presents a straightforward route for extraction, classification and quantification of hop lipids. Offline LC-GC-MS enables separation of polar, neutral and non-polar lipids, as well as the individual analysis of fatty acid type and content. Unambiguous identification and precise quantification of C14-C22 fatty acids was performed by use of four appropriate internal standards and GC-EI-MS analysis of fatty acid methyl esters.